Duration of therapeutic coma and outcome of refractory status epilepticus. (7th April 2019) - Muhlhofer, Wolfgang G.; Layfield, Stephen; Lowenstein, Daniel; Lin, Chee Paul; Johnson, Robert D.; Saini, Shalini; Szaflarski, Jerzy P.
Summary: Objective: Examine the association of duration of therapeutic coma (TC) with seizure recurrence, morbidity, and mortality in refractory status epilepticus (RSE). Define an optimal window for TC that provides sustained seizure control and minimizes complications. Methods: Retrospective, observational cohort study involving patients who presented with RSE to the University of Alabama at Birmingham or the University of California at San Francisco from 2010 to 2016. Relationship of duration of TC with primary and secondary outcomes was evaluated using two‐sample t tests, simple linear regression, and chi‐square tests. Multivariable linear and logistic regression models were used to identify independent predictors. Predictive ability of TC for seizure recurrence was quantified using a receiver‐operating characteristic curve. Youden index was used to determine an optimal cutoff value. Results: Multivariable analysis of clinical and treatment characteristics of 182 patients who were treated predominantly with propofol as anesthetic agent showed that longer duration of the first trial of TC (27.2 vs 15.6 hours) was independently associated with a higher chance of seizure recurrence following the first weaning attempt ( P = 0.038) but not with poor functional neurologic outcome upon discharge, in‐hospital complications, or mortality. Furthermore, higher doses of anesthetic utilized during the first trial of TC were independently associated with fewer in‐hospital complications ( P = 0.003) and associated with a shorter duration of mechanical ventilation and total length of stay. Duration of TC was identified as an independent predictor of seizure recurrence with an optimal cutoff point at 35 hours. Significance: This study suggests that a shorter duration yet deeper TC as treatment for RSE may be more effective and safer than the currently recommended TC duration of 24‐48 hours. Prospective and randomized trials should be conducted to validate these assertions.